Strategic business improvement plan: a case of HLM Boat Noodle / Sharifah Syafeeqah Syed Ahmad Amir Feisal Al-Idrus and Siti Hajar Allias - Syed Ahmad Amir Feisal Al-Idrus, Sharifah Syafeeqah; Allias, Siti Hajar (2016)
Restaurant industry has developed rapidly in Malaysia. HLM Boat Noodle does not lag behind in providing delicious and fresh dishes that lead to potential to become a very strategic restaurant. The purpose of this research is to identify the drop in sales of the restaurant of HLM Boat Noodle. In order to reach this purpose, research questions focusing factor drop in sales to overall lead in order to find the root cause of tremendous drop for the past twelve months. The restaurant is required to identify the most effective way and strategy to sustain its business and secure high profits. The researchers use various instruments to collect primary and secondary data. The instruments that the researchers use are unstructured interview by using sales data from the restaurant, information from the owner, employees and customer. Moreover, the researchers use SWOT analysis, 5 Why’s and Porter’s Five Forces as a tool to identify the root cause that lead to drop of sales. For recommendation, the researcher use TOWS Matrix and ANSOFF Matrix. Based on these findings, the researchers found out that competition, service quality and food variety is the main factor that contributes to HLM Boat Noodle sales performance that lead to drop in sales. Therefore, this research is a contribution of study to HLM Boat Noodle in terms of improving their sales performance. As a conclusion, the researchers hope this research can be a small contribution to upgrade the sales of HLM Boat Noodle’s restaurant